Assessment of River Plan Changes In Terengganu River Using RS And GIS Method - Mohd Khairul Amri, Kamarudin; Muhammad Barzani, Gasim; Roslan, Umar; Abdul Rahman, Hassan (2017)
River is one of the most multifarious regular systems. The database can help in the appropriate understanding of river plan change and know the stand of Terengganu River, Malaysia. The data collected from Geographic Information System (GIS) and Remote Sensing (RS) database. Analysis of Types of Lateral Activity (TYLAT) techniques and Modes of Meander Movement (MOME) method utilized to identify the advancement of the river arrange changes. Satellite images of 2010 and 2015 used in the study were sourced from USGS web. TYLAT was suitable in analyzing the advancement of the waterways plan changes where the river is an extensive and width river. The method for examination of MOME is more appropriate to be used in smaller categories of the river as for upper, middle and down ranges of the river. The result proved the recognition of features or classification of the main stream of Terengganu River.